2002
DOI: 10.1037/0882-7974.17.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of midlife generativity, intergenerational roles, and caregiving.

Abstract: Items from the California Adult Q-Sort (CAQ) were used to assess psychosocial generativity (E. H. Erikson, 1950) in a sample of educated women at midlife. CAQ scores measured at age 43 demonstrated convergent validity with an inventory measure of generativity assessed at age 53. According to other longitudinal analyses, women who attained a generative stance at age 43 reported greater investment 10 years later in intergenerational roles (e.g., daughter, mother) but not nonintergenerational ones (e.g., friend, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 33 publications
5
48
0
5
Order By: Relevance
“…college caring for their elderiy parents (Peterson, 2002), who scored high on the generativity-concem scale used in the present study. This sample of women with high levels of generativity reported being embedded in a reciprocal network with others, whereby they are not just giving but also receiving.…”
Section: Discussionmentioning
confidence: 99%
“…college caring for their elderiy parents (Peterson, 2002), who scored high on the generativity-concem scale used in the present study. This sample of women with high levels of generativity reported being embedded in a reciprocal network with others, whereby they are not just giving but also receiving.…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, through intimate dyadic unions, one resolves inchoate conceptions of reciprocity, sharing and openness, learning what it is to be connected to others, and thus developing the capacity to fully connect to the wider community through generativity. Accordingly, the positive relationship between generativity and close interpersonal relationships is well established (Cheek & Piercy, 2008;Frensch, Pratt, & Norris, 2007;Kotre, 2004;Peterson, 2002;Peterson & Duncan, 2007;Slater, 2003).…”
Section: Generativity and Agementioning
confidence: 92%
“…Stewart and Vandewater (1993) found that women's post-college commitment to different social roles affected their levels of identity and generativity in mid-life: Women who committed to a family were more concerned with generativity in middle age, whereas women who committed to a career were more concerned with identity. Peterson (2002) suggested that the "stage" of generativity may extend across a wider period of adulthood, rather than being confined to mid-life. Kroger (2002) made a parallel argument about identity; she argued that identity preoccupations might not be limited to adolescents and young adults and that older adulthood is also a time of identity reconstruction.…”
Section: Critiques Of Erikson's Developmental Theorymentioning
confidence: 98%